Demarketing Strategies To Reduce Current Smoking Behavior - Muhammad Johan Widikusyanto (Management Science Research Journal, 2023)
Until now, 8 million people worldwide and 225,700 people in Indonesia each year have died due to smoking. Therefore, research on various strategies that can help suppress smoking behavior is still very much needed, crucial, and urgent. This study aimed to determine the attitudes and smoking behavior of the community and the Demarketing strategies needed to suppress these attitudes and smoking behavior. A survey research design was used to obtain data by distributing questionnaires to active smokers in Indonesia with a total of 300 respondents. The data were analyzed using statistical techniques, with the help of SPSS to determine the attitudes and behavior of smokers. The results showed high smoking behavior in the community, with some even consuming more than 3 packs of cigarettes per day. Although attitudes towards smoking were predominantly negative, there were also surprisingly positive attitudes towards smoking. This condition indicates the need for Demarketing strategies to suppress smoking behavior and positive attitudes towards such behavior. The necessary Demarketing strategies are outlined in this article. Keywords: Demarketing Strategies, Dangers of Smoking, Smoker Attitudes, Smoking Behavior.